Predictors of plant endemism in two west African forest hotspots - Marshall, Cicely A. M.; Dabo, Jonathan; Mensah, Markfred; Ekpe, Patrick; Kpadehyea, James T.; Haba, Ouo Ouo; Bilivogui, David; Hawthorne, William D. (Frontiers in Ecology and Evolution, 2022)
Centres of endemism have been much studied by biogeographers, ecologists, and evolutionary theorists, and are considered conservation priorities. It is therefore important to understand the ecological traits of restricted range taxa, and the landscape-scale drivers of high endemism. Here, we investigate correlates of floristic endemism within two of west Africa’s forest biodiversity hotspots at local scale. We assembled distribution data for 1,042 vascular plant taxa from 114 sample locations within forest reserves of south west Ghana, and for 1,735 vascular plant taxa from 454 sample locations within the Nimba Mountains (Liberia and Guinea). A quantitative index of global endemism called the Genetic Heat Index (GHI) was modelled linearly. We tested the significance of modern climate, altitude and disturbance as factors predicting endemism rates in these two forest reserves. Annual rainfall was significantly and positively related to endemism rates in both south west Ghana and the Nimba Mountains. Altitude was a significant predictor of endemism rates in the Nimba Mountains, with a quadratic relationship highlighting particularly high endemism over 1000m. Local topography rather than altitude was a significant predictor or endemism in SW Ghana, where altitude varies less. Areas of high rainfall and high altitude are geographically restricted across the western African forests, acting as edaphic islands driving spatial isolation. Disturbed vegetation samples had lower endemism rates than undisturbed samples in both Nimba and SW Ghana, and overall pioneer species had wider areas of occupancy than shade-bearing species. Endemism rates increased slightly with each year following clearance. Disturbance thus creates and maintains vegetation types which support a lower proportion of globally rare species in the two biodiversity hotspots surveyed. From the point of view of the conservation of globally rare plants, it is important to keep additional disturbance in the south west Ghana hotspot, particularly Ankasa, to a minimum, as is the current practice, and in the Nimba mountains to establish community forests which may be left relatively undisturbed amid farming and mining activities.